PEMENUHAN HAK KONSTITUSIONAL SISWA MELALUI KURIKULUM MERDEKA BELAJAR (STUDI KASUS DI SMK NEGERI 6 PALU) - Asri (TADULAKO MASTER LAW JOURNAL, 2025)
The purpose of the study was to determine the fulfillment of students' constitutional rights through the implementation of the independent learning curriculum. And knowing the independent learning curriculum that is applied in accordance with Pancasila and the 1945 Constitution. The author uses the Normative Research Method, using a statutory approach and a conceptual approach. The results of the study show that, the fulfillment of constitutional rights to education is guaranteed in the 1945 Constitution of the Republic of Indonesia. Everyone has the right to obtain the same education in accordance with their constitutional rights. The implementation of the independent curriculum is beneficial, independent learning does not mean free to want to learn or not learn. Freedom of learning means independence in thinking. Free learning provides opportunities for students to learn as freely and comfortably as possible according to individual interests and talents without any burden, stress, or pressure from any party. The implementation of an independent curriculum towards the fulfillment of students' constitutional rights has been implemented and is felt to have a direct impact on student readiness both in hard skills and soft skills of students. Tujuan penelitian untuk mengetahui pemenuhan hak konstitusional siswa melalui penerapan kurikulum merdeka belajar. Dan mengetahui kurikulum merdeka belajar yang di terapkan sesuai dengan Pancasila dan Undang - Undang Dasar 1945. Penulis menggunakan Metode Penelitian Normatif, dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual.Hasil penelitian menunjukan bahwa, pemenuhan hak konstitusional terhadap pendidikan dijamin di dalam UUD NKRI Tahun 1945. Setiap orang berhak memperoleh pendidikan yang sama sesuai dengan hak konstitusionalnya. Penerapan kurikulum merdeka dirasakan manfaatnya, merdeka belajar bukan berarti bebas untuk mau belajar atau tidak belajar. Merdeka belajar bermakna kemerdekaan dalam berpikir. Merdeka belajar memberikan kesempatan kepada peserta didik untuk belajar sebebas-bebasnya dan senyaman-nyamannya yang disesuaikan dengan minat dan bakat individu tanpa adanya beban, stres, maupun tekanan dari pihak manapun. Implementasi kurikulum merdeka terhadap pemenuhan hak konstitusional siswa sudah dilaksanakan dan dirasa berdampak langsung pada kesiapan siswa baik secara hard skills maupun soft skills para siswa